A novel COE-D8-fosfomycin conjugate effectively combats first-line antibiotic-resistant uropathogenic Escherichia coli - Lin Ruan; Cun Fan; Jingjie Chen; Yingxia Wang; Yuji Ren; Wenli Yuan; Xiaozhe Xiong; Chunming Guo (PLoS ONE, 2026)
Recurrent urinary tract infections (UTIs) caused by multidrug-resistant uropathogenic Escherichia coli (UPEC) demand novel antimicrobial approaches. This study evaluated the membrane-intercalating conjugated oligoelectrolyte COE-D8 against 93 clinical UPEC isolates. While >75% of isolates exhibited high-level resistance to first-line antibiotics (MIC > 512 μg/mL), 94.6% remained susceptible to COE-D8 at ≤32 μg/mL. COE-D8 eliminated bacteria fourfold faster than standard antibiotics through membrane disruption driven by a dimensional mismatch with the lipid bilayer. To mitigate the inherent cytotoxicity of COE-D8 alone, we developed a synergistic co-administration strategy with fosfomycin. This approach achieved a significant dose-sparing effect, rescuing 7-day murine survival from 40% to 80% in safety models without compromising efficacy. Furthermore, resistance induction studies identified a high barrier to adaptation, with survival primarily mediated by mzrA mutations. These findings establish the COE-D8/fosfomycin combination as a host-friendly, mechanism-driven strategy against refractory UPEC.